A content analysis of internet information sources on medical cannabis - Daniel J. Kruger; Ilana M. Moffet; Liliah C. Seluk; Lara A. Zammit (BMC, 2020)
Abstract Background Medical cannabis users report that their knowledge regarding cannabis is predominantly from their own personal experiences and the Internet. Objective We summarize and describe information found through Internet searches on medical cannabis in English language websites. Methods We used terms related to medical cannabis in the Google search engine between November and December 2019. Resulting websites were catalogued and coded for content, including mentions of health and medical conditions, pharmacology, dosage, harmful or adverse effects, harm reduction techniques, cautions or warnings, products for sale, and credentials. Results We coded 344 web pages on 179 unique websites. Cannabis was mentioned for the treatment of 151 different medical and health conditions, only four of the twenty most frequently mentioned conditions have received substantial empirical support for cannabis or cannabinoid treatment. Information content varied widely across sites, only a small proportion of sites included information on pharmacology, dosage, risks, and other aspects that are requirements for pharmaceutical drugs. Information provided was only moderately related to conclusions in the emerging scientific literature. Conclusions Given the rise in cannabis use within the U.S. and the reliance on the Internet as a source of information, considerable efforts are needed to provide accurate on-line cannabis education to minimize harms and maximize benefits for individuals and society.